Factors determining poor prognosis in scorpion sting in coastal Andhra Pradesh - Kumar, Chandra Mohan; Prasad, Naveen S V (Indian Journal of Child Health, 2016)
Introduction: Scorpion stings are a major public health problem and a common emergency in India and other tropical countries. In India, red scorpions are more prevalent, and their venom is more likely to cause cardiovascular complications and mortality. Objective: There are very few studies regarding predictors of poor prognosis. Hence, this study was designed which aimed to identify these factors. Materials and Methods: In this hospital-based, prospective study, children admitted to scorpion sting between December 2009 and November 2010 were included. Relevant information was collected and analyzed. Results: Scorpion stings account for 1 in every 36 admissions. Maximum cases were in 0-3 and 7-9 years age groups with mean of 6.78 years. Red scorpion stings were more common and are associated with more severe presentations. There was considerable variation in sting-prazosin interval (SPI) ranging from 2 to 28 h. If the child’s age was below 6 years, red scorpion sting and SPI >8 h were very significantly associated with a higher incidence of complications such as peripheral circulatory failure, congestive cardiac failure, myocarditis, and acute pulmonary edema. Conclusion: Younger age, red scorpion, and delay in administration of prazosin are predictors of poor prognosis in scorpion stings in children, a common and fatal medical emergency in India.